2018
DOI: 10.1590/1807-3107bor-2018.vol32.0079
|View full text |Cite
|
Sign up to set email alerts
|

Time expended on managing molar incisor hypomineralization in a pediatric dental clinic in Nigeria

Abstract: This study assessed the difference in the number of visits made to a dental care clinic and the time spent providing specific dental treatment for children with and without molar incisor hypomineralization (MIH). Children aged 8 to 16 years who presented at the Pediatric Dental Unit of the Obafemi Awolowo University Teaching Hospital Complex, in Ile-Ife, Nigeria, were eligible for the study. A comprehensive medical and dental history was taken, and each child was clinically examined, diagnosed, and treated acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
2
6
0
5
Order By: Relevance
“…This finding contrasts with the study by Padavala et al (38), who found no differences associated with sex. However, it is close to Morenike et al (39), who found IMH in 58.8% men and 43.9% women.…”
Section: Discussionsupporting
confidence: 90%
“…This finding contrasts with the study by Padavala et al (38), who found no differences associated with sex. However, it is close to Morenike et al (39), who found IMH in 58.8% men and 43.9% women.…”
Section: Discussionsupporting
confidence: 90%
“…15 Moreover, children with MIH make more visits to the dentist. 26 In our sample, 3.1% of the children needed restorative treatment for permanent teeth due to MIH. Previous studies 27,28 have reported that yellow and brown opacities in first permanent molars were at a higher risk for fracture or for carious lesions.…”
Section: Discussionmentioning
confidence: 68%
“…Teeth with MIH generally present greater sensitivity [7], greater tendency to develop carious lesions [8], difficulty in obtaining the anesthetic effect [6,9], and require multiple clinical interventions due to the difficulty in obtaining satisfactory adhesion of restorative materials to the dental substrate [9,10], in addition to longer clinical care [10].…”
Section: Introductionmentioning
confidence: 99%